1999
DOI: 10.1046/j.1365-2141.1999.01284.x
|View full text |Cite
|
Sign up to set email alerts
|

Tandem duplication of the FLT3 gene is found in acute lymphoblastic leukaemia as well as acute myeloid leukaemia but not in myelodysplastic syndrome or juvenile chronic myelogenous leukaemia in children

Abstract: We examined mRNA expression and internal tandem duplication of the Fms-like tyrosine kinase 3 (FLT3) gene in haematological malignancies by reverse transcriptase-polymerase chain reaction (RT-PCR) and genomic PCR followed by sequencing. By RT-PCR, expression of FLT3 was detected in 45/74 (61%) leukaemia cell lines and the frequency of expression of FLT3 was significantly higher in undifferentiated type (B-precursor acute lymphoblastic leukaemia; ALL) than in differentiated type cell lines (B-ALL) (P = 0.0076).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
95
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(101 citation statements)
references
References 25 publications
5
95
1
Order By: Relevance
“…In ALL, ITDs are very rare, with only a handful of pediatric cases having been reported (Xu et al, 1999;Yamamoto et al, 2006). In contrast, 7-9% of the cases harbor Asp835/Ile836 mutations, with an increased frequency in infant ALLs with translocations involving the MLL gene and in high hyperdiploid cases.…”
Section: Discussionmentioning
confidence: 99%
“…In ALL, ITDs are very rare, with only a handful of pediatric cases having been reported (Xu et al, 1999;Yamamoto et al, 2006). In contrast, 7-9% of the cases harbor Asp835/Ile836 mutations, with an increased frequency in infant ALLs with translocations involving the MLL gene and in high hyperdiploid cases.…”
Section: Discussionmentioning
confidence: 99%
“…In ALL, Flt3/ITDs have only been reported in two patients which at closer examination were considered to be biphenotypic leukemia. 20 Though Flt3/ITDs are also observed in childhood AML their frequency is significantly lower when compared to adult AML. Frequencies reported for the Japanese childhood AML population vary between 11% (Kondo et al, seven out of 64 cases studied) 21 and 5.3% (Iwai et al, five out of 94 cases studied).…”
Section: Introductionmentioning
confidence: 99%
“…Several groups reported the presence of FLT3/tyrosine kinase domain (TKD) mutations in 3-20% of MLL-rearranged ALLs, 6,[12][13][14] whereas Stam et al 15,16 together with Bardini et al, 17,18 using high-resolution genomic analysis, showed that FLT3 mutations in MLL-rearranged ALLs do not occur. Despite this emerging controversy, FLT3 is consistently highly expressed in MLLrearranged ALL, and therefore it is not fully resolved whether the constitutive activation of FLT3 in MLL-rearranged ALL is due to the presence of activating FLT3 mutations, or simply due to a transcriptional increased expression of FLT3 in an attempt to provide blast cells with survival and proliferative advantage.…”
Section: Introductionmentioning
confidence: 99%